Advances in abstract intelligence and soft computing - Wang, Yingxu; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'This book brings together the latest research in computer science, theoretical software engineering, cognitive science & informatics and highlights their influence on the processes of natural and machine intelligence'--Provided by publisher.
A formal knowledge representation system (FKRS) for the intelligent knowledge base of a cognitive learning engine / Yousheng Tian ... [et al.] -- Sparse based image classification with bag-of-visual-words representations / Yuanyuan Zuo, Bo Zhang ... [et al.] -- Quotient space-based boundary condition for particle swarm optimization algorithm / Yuhong Chi ... [et al.] -- Medical image classification using an optimal feature extraction algorithm and a supervised classifier technique / Ahmed Kharrat ... [et al.] -- EEG feature extraction and pattern classification based on motor imagery in brain-computer interface / Ling Zou ... [et al.] -- Inconsistency-induced learning for perpetual learners / Du Zhang, Meiliu Lu -- Toward automatic answers in user-interactive question answering systems / Tianyong Hao ... [et al.] -- On cognitive models of causal inferences and causation networks / Yingxu Wang -- On localities of knowledge inconsistency / Du Zhang -- Adaptive study design through semantic association rule analysis / Ping Chen, Wei Ding, Walter Garcia -- Qualitative reasoning approach to a driver's cognitive mental load / Shinichiro Sega -- Intelligent fault recognition and diagnosis for rotating machines using neural networks / Cyprian F. Ngolah, Ed Morden, Yingxu Wang -- Empirical studies on the functional complexity of software in large-scale software systems / Yingxu Wang, Vincent Chiew -- The formal design model of a file management system (FMS) / Yingxu Wang -- The formal design model of doubly-linked-circular lists (DLC-Lists) / Yingxu Wang -- Petri nets and discrete events systems / Juan L. G. Guirao, Fernando L. Pelayo -- The formal design models of a universal array (UA) and its implementation / Yingxu Wang, Jason Huang, Jingsheng Lei -- The formal design models of tree architectures and behaviors / Yingxu Wang, Xinming Tan -- Four-channel control architectures for bilateral and multilateral teleoperation / Yuji Wang, Fuchun Sun, Huaping Liu -- Entropy quad-trees for high complexity regions detection / Rosanne Vetro, Dan A. Simovici, Wei Ding -- Sitting posture recognition and location estimation for human-aware environment / Yusuke Manabe, Kenji Sugawara -- Generic cabling of intelligent buildings based on ant colony algorithm / Yunlong Wang, Kueiming Lo -- Potentials of quadratic neural unit for applications / Ricardo Rodriguez, Ivo Bukovsky, Noriyasu Homma -- A value-based framework for software evolutionary testing / Du Zhang -- Comparison of promoter sequences based on inter motif distance / A. Meera, Lalitha Rangarajan.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed December 17, 2012).
Keywords: Soft computing; Artificial intelligence; Software engineering; Autonomous agent systems; Cognitive informatics; Human-aware environments; Neural informatics; Neural networks; Software and intelligence sciences